Moral Philosophy in Serat Darmawasita for Java Community Development - Purwadi, Purwadi (International Journal of Multidisciplinary Sciences, 2025)
This article attempts to discuss the moral philosophy contained in Serat Darmawasita. Philosophical methods are used to explore ethical values so that they can be used as a means of fostering the spiritual mentality of the Javanese people. Hermeneutic theory is applied to analyze the noble teachings inherited from Mangkunegara IV. Serat Darmawasita, which is written in the form of macapat song, is always relevant when it is linked to the spirit of fostering noble character. The younger generation does need moral development to welcome a brighter future. The discussion result of Serat Darmawasita which is analyzed philosophically and ethically is an effective medium for fostering national character. The ethical values discussed are a means to strengthen national identity. The ethical teachings in Serat Darmawasita are very relevant when linked to the efforts of the national spirit and other traditional ethical values. The moral philosophy in Darmawasita can contribute to the life of the nation and state.